DAKWAH STRATEGIES FOR ADDRESSING STUDENTS’ RELIGIOUS PROBLEMS AT SMA NEGERI 1 BADAU, KAPUAS HULU - Saripaini Saripaini; Yuriadi Yusriadi (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2023)
Complex problems that teenagers usually face as they grow physically and mentally. The environment really determines the form of problems and how they deal with those problems. This research aims to get an overview of how the rural environment shapes religious problems among Muslim teenagers in Nanga Badau District, Kapuas Hulu. The research was conducted at SMA Negeri 1 Badau, where the teenagers studied. The method used is a descriptive method with a qualitative approach. Data was obtained through interviews and documentation. The results of the research illustrate that: There are 3 (three) religious problems among Muslim teenagers at SMA Negeri 1 Badau, namely, the problem of difficulty in practicing religion, the problem of weakness of faith, and the problem of implementing religious teachings. The socio-religious environment and information intake are the causes of this problem. Global da'wah through media channels is not yet familiar to students in this rural area.